2017
DOI: 10.2147/amep.s125352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-month educational intervention on outpatient clinicians’ attitudes and behaviors concerning spiritual practices with patients

Abstract: ObjectiveWe report here the impact of an educational training program on attitudes and practices of physicians (MDs) and mid-level practitioners (MLPs) toward controversial spiritual practices, such as practitioner-led prayer, sharing personal religious beliefs, and encouraging patients’ religious beliefs.MethodsIn this single-group experimental study, 427 physicians and 93 MLPs affiliated with the Adventist Health System agreed to complete a questionnaire assessing demographics, practice characteristics, reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…15 Previous studies have found many health-care providers have actually prayed with their patients, ranging from 21% to 47%. 16,17 This is similar to our finding that 42% of residents reported praying with a patient during their residency training.…”
Section: Discussionsupporting
confidence: 88%
“…15 Previous studies have found many health-care providers have actually prayed with their patients, ranging from 21% to 47%. 16,17 This is similar to our finding that 42% of residents reported praying with a patient during their residency training.…”
Section: Discussionsupporting
confidence: 88%